Cartilage calcification is associated with histological degeneration of the knee joint: a highly prevalent, age-independent systemic process. Issue 10 (October 2020) - Hubert, J.; Beil, F.T.; Rolvien, T.; Butscheidt, S.; Hischke, S.; Püschel, K.; Frosch, S.; Mussawy, H.; Ries, C.; Hawellek, T.
Summary: Objectives: To investigate if cartilage calcification (CC) is a systemic process, the purpose of this study was to determine the prevalence and the amount of meniscal/hyaline CC of the knee joint in the general population by high-resolution imaging (DCR) and to evaluate the association between CC with cartilage degeneration and age. Methods: Cross-sectional DCR-study of 180 knee joints of 90 donors (42 female/48 male, mean age 62.3y). Histological hyaline (OARSI) and meniscal (Krenn) cartilage degeneration was determined of all knees. Results: CC was observed in 100% of the donors (bilaterally in 98%), hyaline cartilage calcification (HCC) in 92% and meniscal calcification (MC) in 100%. CC was detected in more than three out of six distinct cartilage areas in 84.4% of all knees. The mean amount of CC correlated between both sides of donors, the different analyzed areas of the knee joint and between the various types of cartilage structures. There was more calcification in meniscal than in hyaline cartilage (factor 5.3) and in the medial than the lateral compartment (factor 1.2). HCC/MC were already detectable with only mild cartilage lesions and the amount correlated with histological cartilage degeneration, but not with age. Conclusions: The present study provides evidence that meniscal and hyaline CC occurs in a pattern that is compatible with CC being a systemically driven process and that meniscal fibrocartilage is more prone to calcification than hyaline cartilage. Furthermore, the age-independent association between the amount of CC and the grade of degeneration in both hyaline and meniscal cartilage, suggests that CC is an obligatory early event in initiating cartilage degeneration.